Cost-effectiveness of emicizumab for the treatment of hemophilia A: a systematic review - Chen, Min; Lin, Yunzhu; He, Guoqian; Huang, Liang; Han, Junyi; Ni, Jiaqi (Frontiers in Public Health, 2025)
BackgroundEmicizumab, a bispecific factor IXa- and factor X-directed antibody indicated for routine prophylaxis of bleeding episodes in people with hemophilia A, can impose a significant financial burden. We conducted a systematic review to evaluate the reporting quality of existing pharmacoeconomic studies on emicizumab, and to synthesize its cost-effectiveness for hemophilia A treatment.MethodsDatabases including PubMed, Embase, Cochrane Library, National Health Service Economic Evaluation Database, Health Technology Assessment, China National Knowledge Infrastructure, VIP China Science and Technology Journal database, and WanFang were searched for pharmacoeconomic studies on emicizumab. The general information, methods, and results of the retrieved studies were analyzed. The reporting quality of the studies was evaluated with the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) 2022 checklist.ResultsA total of 163 studies were retrieved, and 17 studies were further analyzed. Emicizumab was compared to bypassing agents (BPAs), recombinant factor VIII (rFVIII), recombinant factor VIII Fc fusion protein (rFVIIIFc), and gene therapy. The reporting quality of the studies is generally good with an average score of 79.64% (22.3/28) based on the CHEERS 2022 checklist. Current studies revealed that emicizumab prophylaxis was more cost-effective compared to BPAs in people with hemophilia A with inhibitors. However, its cost-effectiveness compared to rFVIII was unclear and varied across different countries. In addition, rFVIIIFc and valoctocogene roxaparvovec were more cost-effective than emicizumab for people with HA without inhibitors.ConclusionEmicizumab prophylaxis was more cost-effective compared to BPAs in people with hemophilia A with inhibitors. Cost-effectiveness analyses with more accurate cost estimations of different countries should provide more convincing evidence for clinical decision-making.Systematic review registrationIdentifier CRD 42023429349, https://www.crd.york.ac.uk/PROSPERO/view/CRD42023429349.